MicroRNA signatures of resveratrol in ischemic heart - Mukhopadhyay, Partha (2011)
Until middle of the last decade, few people had heard of the term microRNA (miRNA), a 21-23bp long conserved RNA. MicroRNAs represent a new paradigm that regulates most physiological processes and has intense potential for medical advancement. Resveratrol, a red wine-derived polyphenolic compound, has been shown to have significant effects in various disease models such as cardioprotection in ischemic heart, diabetes, chemoprevention of cancers, etc. The targets of resveratrol include various pathways and molecules such as sirtuins, FOXOs, and autophagy. The successful application of resveratrol lies in understanding its mechanisms of action through direct and indirect interactions with pathways, including miRNAs. For example, a unique miRNA footprint is present in the heart treated with resveratrol. Targets of those miRNAs have potential implication on the physiological and patho-physiological conditions in health and disease.